Mathematical Optimization Theory and Operations Research : 19th International Conference, MOTOR 2020, Novosibirsk, Russia, July 6–10, 2020, Proceedings /: 19th International Conference, MOTOR 2020, Novosibirsk, Russia, July 6–10, 2020, Proceedings. (2020) - Unknown
No abstract available